A longitudinal study of fan aggression: a test of general strain theory - Shadmanfaat, Seyyedeh Masoomeh Shamila (Deviant behavior, 2022)
This paper employs panel data on Iranian soccer fan hooliganism (i.e., verbal and physical aggression against rivals) to provide a longitudinal test of Agnew’s general strain theory. Structural equation models reveal that the experience of strain, a latent variable comprised of negative life events, victimization, bullying, and economic pressures, is positively associated with fan aggression. Moreover, the effects of these strains are both directly and partially mediated through negative affect (state-based anger).